Forest carbon market in Vietnam: Legal framework, opportunities and challenges - Pham, T. T.; Tăng Thị, K.H.; Nguyễn, C.C. (Center for International Forestry Research, 2022)
This report aims to identify forest carbon potential, review relevant policies, and explore opportunities and challenges for Vietnam to develop and operate a forest carbon market. The report also provides recommendations for Vietnam and other stakeholders on developing effective, efficient and equitable forest carbon policies and projects.